Fitness of B-biotype Bemisia tabaci (Gennadius) to different varieties of tomato, Lycopersicon esculentum Mill - PANG Shu-ting; WANG Shu-qin; GUO Yu-ling; SHI Zu-hua (浙江大学学报. 农业与生命科学版)
The development, survivorship and reproduction of B-biotype Bemisia tabaci (Gennadius) on eleven different varieties of tomato Lycopersicon esculentum Mill were studied at (26±1) ℃, with a photoperiod of 14 h light vs. 10 h dark and a relative humidity of 60% to 80% in the laboratory. The results show that the selectivity of the B. tabaci to the eleven varieties of tomato exhibited significantly difference. The most preferred variety was Huangtuoyuan, and the least preferred one was Zheza203. The developmental periods from egg to adult varied from 21.35 days on Kaite No. 1 to 19.59 days on Zheza207. Life table parameters were calculated as biological attributes for B. tabaci populations fed on different varieties of tomato. The intrinsic rates of increase (rm) of Huangtuoyuan, Kaite No. 1, 903Red, Zheza809 and Zheza203 were 0.4706, 0.4289, 0.4115, 0.3974, 0.3435, respectively. Experimental evidence in the investigation indicates that B. tabaci is best adapted and shows the greatest preference for Huangtuoyuan and the lowest fitness on Zheza203 oppositely. There is obvious difference on traits resistant to B-biotype B. tabaci among tomato varieties.